Yükseköğretimde Kalite İçin Meslek Yüksekokulu Öğrencilerinin Görüşleri - Can, Ertuğ (Muş Alparslan Üniversitesi, 2020)
The purpose of this research is to determine the needs for quality in vocational colleges and to develop suggestions. Qualitative research method was used in the research. The research was conducted in seven different vocational schools of Kırklareli University in 2017-2018 academic year. The data of the research were collected from 120 students with a structured open-ended question and evaluated by content analysis. According to the findings of the research, students'satisfaction, expectations and needs must be met in order to ensure quality in vocational colleges. According to the students, practical education should be given more importance than theoretical education. In addition, according to students, physical and technological opportunities of vocational colleges should be increased, more budget should be allocated, effective communication should be established with students and social, scientific and sportive activities should be given importance. The quality of education in vocational colleges can also contribute positively to the quality of the higher education system. Therefore, a quality-oriented policy should be implemented for vocational and technical education in higher education.

Bu araştırmanın amacı, meslek yüksekokullarında kalite için ihtiyaçları belirlemek ve öneriler geliştirmektir. Araştırmada nitel araştırma yöntemi kullanılmıştır. Araştırma 2017-2018 eğitim-öğretim yılında Kırklareli Üniversitesi’nin yedi farklı meslek yüksekokulunda gerçekleştirilmiştir. Araştırmanın verileri, yapılandırılmış bir açık uçlu soru ile 120 öğrenciden toplanmış ve içerik analizi ile değerlendirilmiştir. Araştırma bulgularına göre, meslek yüksekokullarında kalitenin sağlanabilmesi için öğrenci memnuniyeti, beklenti ve ihtiyaçlarının karşılanması gerekmektedir. Öğrencilere göre, teorik eğitimden daha çok, uygulamalı eğitime önem verilmelidir. Ayrıca, öğrencilere göre meslek yüksekokullarının fiziksel ve teknolojik olanakları arttırılmalı, daha fazla bütçe ayrılmalı, öğrencilerle etkili iletişim kurulmalı, sosyal, bilimsel ve sportif etkinliklere önem verilmelidir. Meslek yüksekokullarındaki eğitimin kalitesi aynı zamanda yükseköğretim sistemindeki kaliteye olumlu katkılar sağlayabilir. Bu nedenle, yükseköğretimde meslekî ve teknik eğitim için kalite odaklı bir politika uygulanmalıdır.
Opinions of Vocational College Students for Quality in Higher Education
anemon
Keywords: quality in education; vocational colleges; quality in higher education; vocational education; eğitimde kalite; meslek yüksekokulları; yükseköğretimde kalite; meslekî eğitim